Pengaruh Senam Nifas Terhadap Involusi Uterus Pada Ibu Post Partum Primipara Di Ruang Mawar Rsud Majalaya Kabupaten Bandung Tahun 2021 - Yeni Hendriani; Fitri Komalasari (Pusat Riset dan Inovasi Nasional, 2021)
Puerperal gymnastics is a series of body movements performed by maternal postpartum that aims to restore and maintain muscle strength associated with childbirth. Results of preliminary studies commencing on January to April 2016, there are six post-partum mothers experience postpartum hemorrhage. A puerperal gymnastics counseling to postpartum mothers has been done but not all postpartum mothers doing gymnastics parturition. This is due to postpartum mothers are not unaware that puerperal gymnastics will affect the muscles needs for oxygen, blood flow becomes smooth so it can help the process of health recovery after childbirth. The purpose of this study is to find the effect of puerperal gymnastics to involution of uterus to primipara maternal in Majalaya Hospital Bandung District in 2016. The type of research is a quasi-experimental design with posttest only non-equivalent control group method. Sampling technique in this study using purposive sampling with the number of sample in this study as many as 20 people. From the results, it is found that an average reduction of TFU intervention group is 6.3 cm while the control group is 9.6 cm. Statistical test results of T-Independent Samples Test are t count = 8.222, t table = 1.734 which means t count > t table and sig.t count ρ Value (0.000<0.05) and there are differences in the effect of puerperal gymnastics to the involution of uterus to the primipara maternal in Rose Room of Majalaya Hospital 2016, seen from the decline of TFU between the puerperal gymnastics intervention group and the control group that does not given puerperal gymnastics. Advice for the health workers in the Rose Room is to make SOP of puerperal gymnastics and implement puerperal gymnastics by implementing puerperal gymnastics programs of postpartum mothers which is beneficial to the healing process of self-postpartum.